Exploring neuroprotective activity of ethanolic rhizome extract of Alpinia calcarata in cisplatin-induced peripheral neuropathy in rats - Apurwa Shyam Dhavale, M. G. Hariprasad, Rajendran Ramaswamy (Journal of Applied Pharmaceutical Science, 2024)
This study aims to determine the neuroprotective activity of Alpinia calcarata (Haw.) Roscoe rhizome ethanolic extract (ACREE) using cis-diamminedichloroplatinum II (CDDP, cisplatin)-induced peripheral neuropathy (CIPN) rat (Wistar albino) models. The rats were maintained in suitable laboratory conditions (12 hours light/dark cycle, 25ºC ± 2ºC temp) with a nutritional diet and water ad libitum, divided into four groups (n = 6) for the experiment. After 7 days of acclimation, groups II, III, and IV were injected with 2 mg/kg cisplatin intraperitoneal, with 2 ml saline (oral) on days 8, 15, 22, 28, and 36 along with ACREE oral doses of 250 mg/kg (to group III), and 500 mg/kg (to group IV) daily from day 8 to 42. Physical, behavioral, biochemical, and electrophysiological parameters were evaluated, and sciatic nerve histopathology was studied. Statistical analysis using one-way variance analysis (ANOVA) showed improvement in CIPN condition due to ACREE treatment in nerve conduction velocity (p < 0.001), grip strength (p < 0.001), rota rod performance (p < 0.01), hot and cold hyperalgesia (p < 0.001), inflammatory markers high sensitivity C reactive protein, tumor necrosis factor-α, and interleukin (p < 0.001), and oxidative stress parameters catalase, glutathione, superoxide dismutase, and malondialdehyde (p < 0.001). Histopathology study revealed preservation of neuro-morphology and myelin sheath and minimal inflammatory effect in treatment groups over diseased. This novel finding could be crucial in improving cancer patient survival and life quality. Further research is recommended to elucidate the precise mechanisms of ACREE’s protective effects and explore its integration with existing cancer treatments to effectively neutralize the impact of cisplatin-induced peripheral neuropathy.
Keywords: Alpinia calcarata, cisplatin, peripheral neuropathy, cis-diamminedichloroplatinum II, neuroprotection